(3LhGQ GdCNjGQ aj OGQ GdbQGQs - (3GHf CHj MLdI , CMeO Hf jMji Hf CHj HcQ GdJdeSGfj, TgGH GdOjf CHh GdYHGS,J (B776 (3g` s ((3EHQGgje Hf eMeO CHj GdCajGd GdeGdci s)
(3ChdgG (B:s
(3hHYO ,adeG eGJ hdOi eMeO GdhdO GdSYjO GdTgjO ,HGdWGYhf GdMGOK HGdbGgQI GdeMQhSI ai TgQ QLH GdCUH SfI s
(3BNQgG (B:s
(3Ydjg efi SdGe OGFekG CHOkG eGRf fXe bUjOi MSf eNJJe s
(3hgh cJGH ai efGbH YbHI Hf YGeQ GdLgfi GdUMGHi hef Oaf HLhGQg HGdbQGaI HGdbGgQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B268s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B13 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B6 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B142 s
(3eUOQ GbJfGA GdCUd (B:s
(3QhGb GdeZGQHI (B((3GdCRgQ (B1199) s
Keywords: (3GdJGQjNs